Advances, challenges, and environmental impacts in metal–air battery electrolytes. (August 2022) - Salado, Manuel; Lizundia, Erlantz
Abstract: Efficient energy storage technologies are vital in the current efforts towards decarbonisation. Batteries, as one of the most versatile electrochemical energy storage systems, have the potential to shape the transition from the current climate crisis scenario to a carbon neutral and sustainable future. In particular, metal–air batteries are gaining scientific and industrial interest as promising contenders to the ubiquitous lithium-ion batteries. The electrolyte plays a critical role in metal–air batteries as it determines the battery performance, its safety and the operating lifespan. The low-density, ease of processing, good thermal and electrochemical stability, mechanically stiff but ductile character, electrically insulating properties and tailor-made chemistry make polymers singularly interesting to be applied as a separator/liquid electrolyte pair, gel-electrolytes or solid-electrolytes. Accordingly, in this work the current bottlenecks and challenges in metal–air batteries are presented, with particular emphasis on the electrolyte design. The implementation of aqueous liquid electrolytes, organic liquid electrolytes, polymer membranes soaked in liquid electrolytes, gel-like electrolytes and solid-state electrolytes is discussed and the environmental impacts associated with metal–air batteries are analysed within a Circular Economy perspective. We expect this work can guide future efforts in the development of potentially sustainable next generation metal-air batteries. Graphical abstract: Image 1 Highlights: Defining an appropriate electrolyte composition is one of the most important choices to improve MAB performance. Natural polymers are attractive given their abundant functional groups and ability to form gel and solid electrolytes. Further works should focus on the environmental/cost sustainability and end-of-life scenarios of metal-air batteries.